1991
DOI: 10.1152/ajpendo.1991.261.1.e109
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of omega-3 fish oils on protein kinase activities in vitro

Abstract: We studied the in vitro effects of omega-3 fish oils and other fatty acids on the activity of crude protein kinase C from S49 lymphoma cells, on partially purified enzyme from rat cerebrum, on homogeneous protein kinase C from bovine brain, and, for comparison, on type I adenosine 3',5'-cyclic monophosphate (cAMP)-dependent protein kinase. In the absence of exogenous phospholipid, the fish oils cis-5,8,11,14,17-eicosapentaenoic acid (EPA) and acid (DCHA) enhance the catalytic cis-4,7,10,13,16,19-docosahexaenoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
41
0

Year Published

1994
1994
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 23 publications
7
41
0
Order By: Relevance
“…These studies included fatty acids of the n-6, n-7 and n-9 classes. However, studies on the action of n-3 PUFAs on signal transduction are limited, although modulation of the catalytic activity of protein kinase C and type I cAMP-dependent protein kinase has been demonstrated (Speizer et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…These studies included fatty acids of the n-6, n-7 and n-9 classes. However, studies on the action of n-3 PUFAs on signal transduction are limited, although modulation of the catalytic activity of protein kinase C and type I cAMP-dependent protein kinase has been demonstrated (Speizer et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Concentrations of DHA, EPA, and AA ranged from 0.1 M to 400 M, based on concentrations used in prior in vitro studies with omega-3 fatty acids. 8,9,16 Enzyme activity was measured by quantifying incorporation of 32 P-PO 4 into a synthetic peptide substrate. 17 The reaction mixture consisted of 20 ng of the catalytic subunit of PKC, 20 mM Tris-HCl (pH 7.5), 0.5 mM EGTA, 1 mM EDTA, 2 mM Na 2 PO 4 , deionized H 2 O, 20 M protein substrate, 1 mM ATP, 1 Ci ml −1 gamma-32 P-ATP, 10 mM MgCl 2 .…”
Section: Molecular Psychiatrymentioning
confidence: 99%
“…[1][2][3][4][5][6][7] Preliminary evidence suggests that omega-3 fatty acids may also affect PKC. 8,9 A clinical pilot study, undertaken based on this putative mechanistic commonality, concluded that omega-3 fatty acids may be effective mood stabilizers for patients with bipolar disorder. In a recent 4-month, double-blind, placebo-controlled study, outpatients who received omega-3 fatty acids in addition to stable doses of their baseline medications had a significantly longer period of remaining well than the placebo group, and performed better for nearly every other outcome measure.…”
mentioning
confidence: 99%
“…It seems likely that the effects of fatty acids are due to their incorporation into membrane phospholipids, altering the fatty acid composition and fluidity [42]. In other tissues and cell types such changes have been shown to affect receptor activity (see [44]) and signal transduction mechanisms (see [45,46] (Tables 5 and 6). Such an effect has not been previously reported.…”
Section: Incorporation Of Glycerol By Lymphocytes In Vitromentioning
confidence: 99%